Pharmacology in Peripheral Arterial Disease: What the Interventional Radiologist Needs to Know - Atturu, Gnaneswar; Homer-Vanniasinkam, Shervanthi; Russell, David A. (Seminars in Interventional Radiology, 2014)
Peripheral arterial disease (PAD) is a progressive disease with significant morbidity and mortality. Risk factor control, using diet and lifestyle modification, exercise, and pharmacological methods, improves symptoms and reduces associated cardiovascular events in these patients. Antiplatelet agents and anticoagulants may be used to reduce the incidence of acute events related to thrombosis. The armamentarium available for symptom relief and disease modification is discussed. Novel treatments such as therapeutic angiogenesis are in their evolutionary phase with promising preclinical data.
Keywords: peripheral arterial disease; pharmacotherapy; antiplatelet therapy; symptom relief; gene therapy; interventional radiology